DEVELOPMENT OF TAJWID MATERIAL LEARNING VIDEO BASED ON CAPCUT APPLICATION FOR ELEMENTARY SCHOOL STUDENTS - Silvia, Faizatun Nuris; Fahyuni, Eni Fariyatul; Nadlif, Ainun (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2023)
This study aimed to analyze video needs, design videos, analyze video development and analyze the implementation of tajwid material learning videos in the Reading and Writing Qur'an (BTQ) subject. This type of research used research and development methods or is called R&D (Reseach and development) with the ADDIE development model which consists of five stages, namely Analysis, Planning, Development, Implementation and Evaluation. Data collection in this study was based on the validation of media experts and material experts as well as questionnaires from the results of limited trials. The results of this study indicated that based on an analysis of the needs of students, materials and media, as well as adjustments to media design based on the characteristics of students, it has resulted in learning video products that have obtained a media expert eligibility percentage of 86% with a very valid category and material experts of 96% with very valid category. In terms of product practicality, it has known that the tajwid learning videos developed are very interesting and make it easier for students to understand recitation material. This was obtained based on the percentage results by 20 students of 96.2% in the very practical category. Thus, the learning video for tajwid material that has been developed with the CapCut application is considered to have met the eligibility and practical requirements so that it can be used in the learning process.